Al Jam’iyatul Washliyah Cadre Training Model: Analysis of Militantion and Sustainable Curriculum - Yusra Jamali; Sri Nanda Piga Putri; Adnin AS; Jhon Wahidi (Sustainable, 2024)
This research is a literature study on the Al Jam'iyatul Al Washliyah cadre model. The method used in this study is a descriptive method that attempts to describe and emphasize the pattern, model, curriculum of training and cadre formation carried out by Al Washliyah. While the sources and information are obtained from formal documents of Al Washliyah cadre formation, syllabus or curriculum applied in Al Washliyah cadre formation and the results of the conference and scientific books published by Al Washliyah or other valid sources to be used as reference materials. The results of this study indicate that there is still a tradition and tendency for Al Washliyah cadres to foster militancy, consistency and commitment to the Al Washliyah movement model. However, on the other hand there are still weaknesses that Al Washliyah faces challenges in preparing a more contributive, communicative, participatory and collective Al Washliyah cadre formation curriculum. In fact, Al Washliyah has a mental model as a liaison, mediator, enlightener and illuminator, and reformer in the fields of preaching, improving human resources, education and teaching, community economics, and information technology literacy and digitalization.